Benarkah Bullying Victim Mengancam Interaksi Sosial Remaja? - Fajriana Ougtsa Al Madya; Nurul Aiyuda; Fatin Hanifah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract.Individual who was ostracized in the social environment tend to have difficulty in living friendships so they tend to spend a lot of time alone and become targets for various aggressive behavior such as bullying victims. Bullying victim had several types, one of them was the type of teasing (satire), namely mocking, insulting, harassing, and shouting, so that they have negative impact on social interaction on adolescents. While social interaction was the key to all social life and good social interaction skills. It is needed when hanging out with people around so as to form a friendship for teenagers. This study aims to examine the relationship between social interaction and bullying victim in Riau teenagers. The subjects in this study were 210 respondents, 46 male and 164 female, Riau teenagers with age range of 18-24 years. It used purposive sampling to collect sample. The result of this study indicates that there was a significant relationship between social interaction and bullying victims in Riau adolescents, It means that the research hypothesis is accepted. The implication of this research that it was known that bullying victims really need social interaction in order to feel brave or not experience difficulties when in their surroundings. Abstrak. Individu yang dikucilkan dalam lingkungan sosial memilih menghabiskan banyak waktu sendirian sehingga menjadi sasaran berbagai tingkah laku agresif, disebut sebagai bullying victim. Bullying victim memiliki beberapa tipe salah satunya adalah tipeteasing : mengejek, menghina, melecehkan, meneriaki. Sehingga berdampak buruk terhadap interaksi sosial remaja. Sementara interaksi sosial kunci dari semua kehidupan sosial dan interaksi sosial yang baik dibutuhkan ketika bergaul dengan lingkungan sekitar sehingga membentuk suatu pertemanan bagi remaja.Tujuan penelitian untuk melihat hubungan antara interaksi sosial dengan bullying victim pada remaja Riau. Subjek penelitian ini sebanyak 210 responden yakni 46 laki-laki dan 164 perempuan remaja Riau dengan rentang usia 18-24 tahun. Teknik sampel menggunakan purposive sampling. Hasil penelitian ini menunjukan adanya hubungan signifikan interaksi sosial dengan bullying victim pada remaja Riau, demikian hipotesis penelitan diterima. Implikasi penelitian ini, maka diketahui bahwa bullying victim sangat memerlukan interaksi sosial agar individu tidak mengalami kesulitan saat berada di lingkungan sekitarnya.